The Association Between Anticoagulation Therapy, Maternal Characteristics, and a Failed cfDNA Test Due to a Low Fetal Fraction. Issue 3 (March 2018) - Burns, Whitney; Koelper, Nathanael; Barberio, Andrea; Deagostino-Kelly, Mary; Mennuti, Michael; Sammel, Mary D.; Dugoff, Lorraine
Abstract : (Abstracted from Prenat Diagn 2017;37:1125–1129) Fetal cell-free DNA (cfDNA) screening has been established as a screening method for trisomies 13, 18, and 21, as well as sex chromosome aneuploidies. Despite its rapid technological advancement since becoming clinically available in 2011, some women do not receive valid results after undergoing cfDNA testing because of a low fetal fraction (FF).